Effects of Nutritional Interventions in Older Adults with Malnutrition or at Risk of Malnutrition on Muscle Strength and Mortality: Results of Pooled Analyses of Individual Participant Data from Nine RCTs - van Zwienen-Pot, Judith I.; Reinders, Ilse; de Groot, Lisette C.P.G.M.; Beck, Anne Marie; Feldblum, Ilana; Jobse, Inken; Neelemaat, Floor; de van der Schueren, Marian A.E.; Shahar, Danit R.; Smeets, Ellen T.H.C.; Tieland, Michael; Wijnhoven, Hanneke A.H.; et al. (Nutrients, 2023)
Nutritional intervention studies in older adults with malnutrition aim to improve nutritional status. Although these studies show a significant gain in body weight, there is inconsistent evidence of clinical effectiveness on muscle strength and mortality. This study aimed to examine the effects of nutritional interventions on muscle strength and risk of mortality in older adults (malnourished or at risk) and explore whether these effects are influenced by participant characteristics. Individual participant data were used from nine RCTs (community setting, hospital and long-term care; duration 12–24 weeks and included oral nutritional supplements, dietary counseling, or both). Handgrip strength (HGS) was measured in seven RCTs and six RCTs obtained mortality data. A ≥3 kg increase in HGS was considered clinically relevant. Logistic generalized estimating equations analyses (GEE) were used to test intervention effectiveness. GEE showed no overall treatment effect (OR 1.11, 95% CI 0.78–1.59) on HGS. A greater, but not statistically significant, effect on HGS was observed for older (>80 years) versus younger participants. No significant treatment effect was observed for mortality (OR 0.78, 95% CI 0.42–1.46). The treatment effect on mortality was greater but remained non-significant for women and those with higher baseline energy or protein intake. In conclusion, no effects of nutritional interventions were observed on HGS and mortality in older adults (malnourished or at risk). While the treatment effect was modified by some baseline participant characteristics, the treatment also lacked an effect in most subgroups.
CRIS-Team Scopus Importer:2023-05-26
Keywords: dietary counseling; nutritional support; nutritional therapy; older adults; undernutrition